2017
DOI: 10.1016/j.ijggc.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The resilience of carbonic anhydrase enzyme for membrane-based carbon capture applications

Abstract: A microbial carbonic anhydrase was immobilized onto the surface of hollow fiber membranes to enhance the absorption rate of carbon dioxide into an aqueous 30 wt% potassium carbonate solvent at pH 10-12. The performance of the immobilized enzyme was investigated over long time frames to determine the suitability of this approach for postcombustion carbon capture. The immobilized enzyme was able to maintain activity for up to 80 days at 25°C even when initially exposed to pH 12, however lost activity rapidly whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…For most of the cases, membrane contactor is applied for gas capture at relatively low pressure and temperature [330 -332]. Various aqueous absorbents have been studied in membrane contactors, including aqueous amine solutions [335,343], amino salt solutions [335 -337], enzyme solutions [338,339], and ammonia solutions [340 -342]. Based on liquid flow direction, there are co-current, cross flow, and counter-current configurations of membrane contactors [343].…”
Section: Ionic Liquid Membrane Contactors (Ilmcs)mentioning
confidence: 99%
“…For most of the cases, membrane contactor is applied for gas capture at relatively low pressure and temperature [330 -332]. Various aqueous absorbents have been studied in membrane contactors, including aqueous amine solutions [335,343], amino salt solutions [335 -337], enzyme solutions [338,339], and ammonia solutions [340 -342]. Based on liquid flow direction, there are co-current, cross flow, and counter-current configurations of membrane contactors [343].…”
Section: Ionic Liquid Membrane Contactors (Ilmcs)mentioning
confidence: 99%
“…This could be due to the drawbacks of low enzyme activity recovery, poor enzyme stability, and membrane wetting. To address these issues, Yong et al [11,27,28] proposed the layer-by-layer electrostatic adsorption method for preparing PP and PSf─polydimethylsiloxane based biocatalytic membranes layer-by-layer coated by mesoporous silica, polyethylenimine (PEI), polystyrene sulfonate, polyallylamine hydrochloride, and CA for CO 2 hydration in GLMC processes. Their experimental results suggested that the immobilization of CA on polymeric membranes can exhibit enhanced stability relative to their free states while maintaining their activity within the film for longer periods [28].…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, Yong et al [11,27,28] proposed the layer-by-layer electrostatic adsorption method for preparing PP and PSf─polydimethylsiloxane based biocatalytic membranes layer-by-layer coated by mesoporous silica, polyethylenimine (PEI), polystyrene sulfonate, polyallylamine hydrochloride, and CA for CO 2 hydration in GLMC processes. Their experimental results suggested that the immobilization of CA on polymeric membranes can exhibit enhanced stability relative to their free states while maintaining their activity within the film for longer periods [28]. Iliuta et al [16] investigated the CA based biocatalytic membrane in hollow fiber membrane bioreactors as a novel approach for CO 2 capture by using a series of simulations with different parameters of hollow fibers and different operation conditions in a multiscale steady-state model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hydrophobic porous membranes, non-porous CO 2 permeable membranes were also explored as GLMC for CO 2 absorption. CO 2 absorption into 30% K 2 CO 3 solvent using a non-porous polysulfone (PSf) HFM coated with a layer of PDMS [132] was 70-90% that of a porous PP HFM, both incorporating immobilized CA through layerby-layer electrostatic adsorption [131]. A 60-µm-thick free-standing non-porous PDMS membrane used in microfluidic devices to separate anesthesia gases from an ionic liquid (IL)-based CO 2 absorption solvent exhibited a 1.9-fold increase in CO 2 affinity when 0.1 mg CA/ g IL was added, while Xenon permeability was not affected [133].…”
Section: Materials and Surface Modificationsmentioning
confidence: 99%